2016
DOI: 10.1177/1460458215627290
|View full text |Cite
|
Sign up to set email alerts
|

Health information seeking and scanning among US adults aged 50–75 years: Testing a key postulate of the information overload model

Abstract: Past research has found that older US adults (aged 50-75 years) exhibit high levels of cancer information overload and cancer worry; however, no study to date has examined whether these perceptions are related to information seeking/scanning. To explore this relationship, older adults ( N = 209, M = 55.56, SD = 4.24) were recruited to complete a survey measuring seeking, scanning, cancer information overload, and cancer worry. Most participants were high-scan/seekers (40.2%) followed by low-scan/seekers (21.1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 66 publications
3
27
0
2
Order By: Relevance
“…A strength of this study was the diverse sample, reflecting an ethnically diverse, low income, low education, and rural population. The diverse community sample used in this study addresses an important limitation that surrounds previous information overload work, the potential bias and inequalities introduced by only sampling highly educated, Caucasian participants [21,23,24,52]. However, a corresponding limitation is that the study did not randomly sample from the U.S. population as a whole and therefore may not be generalizable nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this study was the diverse sample, reflecting an ethnically diverse, low income, low education, and rural population. The diverse community sample used in this study addresses an important limitation that surrounds previous information overload work, the potential bias and inequalities introduced by only sampling highly educated, Caucasian participants [21,23,24,52]. However, a corresponding limitation is that the study did not randomly sample from the U.S. population as a whole and therefore may not be generalizable nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…The model of information overload [ 19 , 20 ] explains the nature of information overload by relying on the limited cognitive capacity of human beings, which hinders the proper processing of information-namely, encoding, storage, and retrieval. According to Lang [ 21 ], cancer information needs large amounts of cognitive resources for individuals to understand and store the information in memory because of its highly arousing and complex content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for the influence of socio-demographics, studies have shown relatively consistent results. Generally, those who are older [ 7 , 20 ], less educated [ 6 , 7 , 9 , 22 ], and of lower socioeconomic status [ 8 , 9 ] perceive greater information overload. People in poorer physical and mental health conditions also tend more to suffer from information overload [ 7 , 9 ], and trait anxiety also successfully predicts information overload [ 2 , 6 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies suggest that HIO may be related to seeker health information literacy (HIL) [21,26]. HIL is defined as the degree to which individuals can obtain, process, understand, and communicate about health-related information needed to make informed health decisions [18,27]. HIL pertaining to health content delivered by means of the internet is termed electronic health information literacy (EHIL) [28,29].…”
Section: Introductionmentioning
confidence: 99%